A Numerical Investigation of Thermal Performance of Earth-Air Heat Exchanger - Tasdelen, F.; Dagtekin, I. (Springer Heidelberg, 2019)
Today, earth-air heat exchangers (EAHEs) are important heat exchangers used in the air-conditioning of buildings and can be seen in different types and capacities. Thermal comfort is perceived as the comfort of human beings under given roomconditions, namely average temperature and relative humidity. For example, the value of average comfort temperature in a room is between 294 and 296 K. The main objective of this analysis is not to obtain the lower air temperature of medium, rather to obtain comfort temperature interval of 294-296 K. This thermal comfort temperature has been achieved at nearly all channel outlets in 1m depth. For the numerical analysis of EAHE, the maximum mean air temperature of July of the city of Elaz was used. Computational fluid dynamics ANSYS FLUENT 12.1 program was chosen to examine the thermal comfort condition of a typical building. In the analysis of the thermal performance of the EAHE, examinations were made for different earth depths (H=1, 2, 3m). PVC was chosen as the EAHE channel material. The numerical model was solved in three dimensions in the steady-state condition using different Reynolds number values (Re=5x103,104,15x103,2x104,4x104,6x104,105) in the turbulent flow. It was determined that the best thermal performance is at the smallest air inlet velocity. According to the numerical results, it was found that the cooling energy consumption required to provide thermal comfort condition for the typical building is reduced.
Keywords: CFD; Earth; Earth-air heat exchanger; Passive cooling systems; Temperature; Thermal comfort